Entamoeba histolytica EhCP112 Dislocates and Degrades Claudin-1 and Claudin-2 at Tight Junctions of the Intestinal Epithelium - Cuellar, Patricia; Hernández-Nava, Elizabeth; García-Rivera, Guillermina; Chávez-Munguía, Bibiana; Schnoor, Michael; Betanzos, Abigail; Orozco, Esther (Frontiers in Cellular and Infection Microbiology, 2017)
Abstract During intestinal invasion, Entamoeba histolytica opens tight junctions (TJs) reflected by transepithelial electrical resistance (TEER) dropping. To explore the molecular mechanisms underlying this, we studied in vitro and in vivo the damage produced by the recombinant E. histolytica cysteine protease (rEhCP112) on TJ functions and proteins. rEhCP112 reduced TEER in Caco-2 cells in a dose- and time-dependent manner; and EhCP112-overexpressing trophozoites provoked major epithelial injury compared to control trophozoites. rEhCP112 penetrated through the intercellular space, and consequently the ion flux increased and the TJs fence function was disturbed. However,, macromolecular flux was not altered. Functional in vitro assays revealed specific association of rEhCP112 with claudin-1 and claudin-2, that are both involved in regulating ion flux and fence function. Of note, rEhCP112 did not interact with occludin that is responsible for regulating macromolecular flux. Moreover, rEhCP112 degraded and delocalized claudin-1, thus affecting interepithelial adhesion. Concomitantly, expression of the leaky claudin-2 at TJ first increased and then it was degraded. In vivo, rEhCP112 increased intestinal epithelial permeability in the mouse colon, likely due to apical erosion claudin-1 and claudin-2 degradation. In conclusion, we provide evidence that EhCP112 causes epithelial dysfunction by specifically altering claudins at TJ. Thus, EhCP112 could be a potential target for therapeutic approaches against amoebiasis.